Symptoms of PBC – Pathophysiology and management. (June 2018) - Khanna, Amardeep; Leighton, Jess; Lee Wong, Lin; Jones, David E.
Abstract: Primary biliary cholangitis is a chronic cholestatic liver disease characterised by progressive bile duct damage and, ultimately, biliary cirrhosis. Though up to fifty percent of the patients can be asymptomatic at presentation, symptoms when present are frequently debilitating with significant impact on quality of life and functional status. Characteristic symptoms include pruritus, fatigue and an increasingly recognised mild cognitive impairment. With the exception of pruritus, the "classic" cholestatic symptom, therapeutic options to treat PBC related symptoms are currently limited leaving patients with often significant residual problems. Symptoms can frequently contribute to depression and social isolation further compounding the quality of life impairment. There is need to better understand the current therapeutic options available in order to optimise their use, and to explore newer avenues to understand the pathophysiology of the symptom-generating processed in PBC in order to develop new therapies.